Potable moving ladder / Muhammad Fahmi Ahmad Faizal ... [et al.] - Ahmad Faizal, Muhammad Fahmi; Mohd Jonid, Mohd Asyraf; Zamzuri, Fakhrul Fahmi; Norkhairizal, Putri Nurin Qurratu’ Aiini; Tarmizi, Athilah Hidayah
As stated, the use of a ladder is not completely safe for everyone to use it. 14 deaths have occurred in one country averagely internationally. To make a ladder usable for everybody, the strongest factor is the weight of the ladder. A weight of a ladder has been weighing down the ability to carry to only strong human bodies. This leads to need of help for a less strong person to carry the equipment. A weight of a ladder depends on the material in use in building it. The most common materials that are in use are metal (aluminium), timber and the most popular in the industry these days is fiberglass. Although that, use of metal is less heavy than fiberglass. With aluminium as the material of the ladder, it can be portable for more people than fiberglass ladder. This problem can also be solved by making a ladder movable. When a ladder is portable, the weight someone is carrying will be less and the burden to face in moving a ladder to another desired place is no more. A common ladder has a few of steps and a tiny top cap on the top. These features have also been disabling more people to use the ladder. With a little more features added onto a ladder, people like old folks and with minor disability can use a ladder with no worries of accidents. A feature that can be added is a feature that enable a person to climb up the steps on a ladder with better safety such as a place to hang on while slowly climbing up. Other than that, a wider top cap can also be important. This is due to the safety of a person can be improved when less movement is done. Top cap is often used as a platform to place tools. With more space for more tools to be placed, less movement can be helped. A support to let a person hold onto while operating at the high steps can also be helpful in a lot of way. When a person with minor disability is using a ladder, they would expect a better stability which can be gotten from a support.